청소년 대상 탄소중립 숲교육 효과 및 만족도 분석 - 최재혁; Jae Hyeok Choi; 하시연; Si Yeon Ha (한국산림과학회지, 2025)
본 연구는 초등학교 4~6학년 학생과 중학생을 대상으로 탄소중립 숲교육의 효과를 확인하는 데 목적이 있다. 산림청은 2022년 탄소중립 중점학교 및 시범학교를 대상으로 숲교육 프로그램을 개발하고 학교 현장에서 교육을 진행하였다. 프로그램의 교육 효과를 검증하기 위해 숲에 대한 인식, 탄소중립 숲교육 효과 척도(지식, 태도, 행동), 교육 만족도를 조사하였으며, 프로그램 사전·사후 설문에 모두 응답한 895명의 데이터를 분석하였다. 분석 결과, 워드클라우드를 활용한 숲인식 조사에서 프로그램 참가 후 탄소중립 관련 단어의 출현 빈도가 증가하여, 프로그램이 탄소중립 개념 확산에 기여했음을 확인할 수 있었다. 탄소중립 숲교육 효과는 지식, 태도, 행동의 모든 영역에서 통계적으로 유의미한 변화가 나타났다(p<.01). 초등학교 4~6학년과 중학생을 구분하여 분석한 결과 두 집단 모두 모든 영역에서 긍정적인 변화를 보였으나, 태도 변화에서는 초등학생과 중학생 간 유의미한 차이가 나타났다(p<.05). 또한, 초등 4~6학년 학생의 만족도가 중학생보다 높은 것으로 나타났다. 결론적으로, 탄소중립 숲교육은 초등학생과 중학생의 탄소중립에 대한 인식을 제고하고, 지식, 태도, 행동의 변화를 유도하는 데 효과적인 교육 프로그램임을 확인하였다. 본 연구는 탄소중립 숲교육의 중요성과 효과를 실증적으로 검증함으로써, 향후 탄소중립 숲교육 활성화를 위한 기초자료를 제공했다는 점에서 의의가 있다. This study examined the effectiveness of carbon-neutral forest education for upper elementary (grades 4-6) and middle school students. In 2022, the Korea Forest Service developed and implemented a forest education program in carbon-neutral model schools and pilot schools. To evaluate the educational impact of this program, the study conducted pre- and post-surveys to assess the students' perceptions of forests, effectiveness of the program (including on knowledge, attitudes, and behaviors), and their satisfaction with the program. The analysis included 895 students who completed both the pre- and post-surveys. The results of a word cloud analysis revealed that, after participating in the program, the use of carbon-neutral-related words increased among students, indicating that the program contributed to spreading awareness of carbon neutrality. The effectiveness of the program was statistically significant across all domains of knowledge, attitudes, and behaviors (p < 0.01). Both elementary and middle school students exhibited positive changes in all domains. However, the change in attitude showed a statistically significant difference between the two groups (p < 0.05). Additionally, the elementary students reported higher satisfaction with the program than the middle school students. Thus, the carbon-neutral forest education program was found to be an effective educational tool for enhancing students' awareness of carbon neutrality and fostering changes in their knowledge, attitudes, and behaviors. This study provided a foundational resource for promoting and expanding future carbon-neutral forest education by empirically verifying its importance and effectiveness.